1997
DOI: 10.1007/bf03173773
|View full text |Cite
|
Sign up to set email alerts
|

Does participating in an undergraduate elementary science methods course make a difference?

Abstract: Beginning with the question, does it make a difference what skills are developed or in what sequence they are introduced, the results of this study show that science teaching skills associated with personal survival are highly visible in both the expectations of prospective teachers and in what they value from a science methods course. It is equally clear that as they become confident in their personal science knowledge base, and competent in translating this into instructional plans for children, prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 15 publications
1
7
0
2
Order By: Relevance
“…However, we concur with Butts, Koballa & Elliot (1997) that taking more courses does not necessarily predict how well preservice teachers teach science to children. However, we concur with Butts, Koballa & Elliot (1997) that taking more courses does not necessarily predict how well preservice teachers teach science to children.…”
Section: Theoretical Frameworksupporting
confidence: 85%
“…However, we concur with Butts, Koballa & Elliot (1997) that taking more courses does not necessarily predict how well preservice teachers teach science to children. However, we concur with Butts, Koballa & Elliot (1997) that taking more courses does not necessarily predict how well preservice teachers teach science to children.…”
Section: Theoretical Frameworksupporting
confidence: 85%
“…Studies throughout K-16 have shown that inquiry-based science activities had positive effects on students' cognitive development, self-confidence, science achievement, science process skills, and conceptual understanding of science knowledge as a whole compared with students taught using a traditional approach (Bohning & Hale, 1998;Butts, Koballa, & Elliot, 1997;Ertepinar & Geban, 1996;Geban, Askar, & Ozkan, 1992;Gibson & Chase, 2002;Jarrett, 1999;Moore & Watson, 1999;Saunders & Shepardson, 1987). Similar findings were found among preservice science teachers.…”
Section: Attitudes Toward Inquiry-based Approach In Science Educationmentioning
confidence: 66%
“…The study of emotion to explore the emotional labor teachers experience is particularly important in science teacher education given that some recent work (Anderson, Smith, & Peasley, 2000;Butts, Koballa, & Elliott, 1997;Koballa & French, 1995;Nichols & Tippins, 2000;Richmond et al, 1998;Tippins, Nichols, & Dana, 1999;Zembylas & Barker, 2002) emphasizes that a focus on the personal concerns of prospective teachers makes a difference in the confidence with which they approach teaching science. An investigation of teacher emotion in pre-service and in-service science education will clarify how teachers' curricular actions and decisions are associated with abstract conceptualizations of their roles in the classroom.…”
Section: Emotion Metaphorsmentioning
confidence: 98%